The Pengaruh Kualitas Udara Ambient dan Karakteristik Individu Terhadap Kapasitas Parkir Kota Makassar Pulih - aisyah, Aisyah; Ikhtiar, Muhammad; Fachrin, Suharni a. (Window of Health : Jurnal Kesehatan, 2018)
Maximal air volume is KVP, issued at the first one second when the maximum ekspirasi after doing the maximal inspiration and the measurement can be done by spirometri. Factors that can affect a person's lung function among other things the age, gender, smoking habits, environment, and pulmonary disease, working period, APD. The purpose of this research was to analyze the influence of the ambient air quality and characteristics of the individual against the vital capacity of lungs on parking, this research is research observational analytic with cross sectional approach. The collection of data using questionnaires and measurements of air quality CO and NO2. The sample of this research as many as 50 people using Total Sampling. Analysis on statistical tests using test bivariat chi-square and multivariate analysis using linear regression statistical tests. The results of the research showed there are between the age of influence with the KVP retrieved value R square 127 Furthermore there is no relationship between time of work with the KVP i.e. p = 0518 > = 0.05, then there is no relationship between smoking habit with the KVP, no relationship between air quality with the KVP and there is no relationship between APD with the KVP i.e. p = 0. 362 and there are influences between a history of pulmonary disease with KVP the values R square 583 times compared to normal lung diseases history the next variable is the most influential pulmonary disease history against KVP with significant value 0.00 meaning hypothesis accepted because the value of sig p value 0.05 <. This research was menyarankani so ukang parking can keep his physical condition by doing olaraga, control the habit of smoking and the use of masks. As well as often checked health in health service center closest to you.